Pre-labor Rupture of Membrane in Aminu Kano Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Prelabor rupture of the membranes (PROM) is the rupture of fetal membranes before the onset of labor and it complicates about 8% of pregnancies at term and 3% of pregnancies before term. This study evaluated the maternal characteristics and pregnancy outcomes in different gestational ages in patients with PROM in Aminu Kano teaching hospital Kano, Nigeria, between August 2015 and July 2017.Materials and Methods:This was a retrospective analysis of all cases managed for PROM between 1stAugust 2015 and 31stJuly 2017 in the department. All patients admitted with PROM were included. Information extracted includes maternal demographic and obstetrical variables, duration of conservative management, mode of delivery, birth weight, Apgar score. Data was collated and analyzed using SPSS version 22. Descriptive variables were presented in tables and tests of significance were done using Chi-square test.Results:A total of 6,658 deliveries were recorded during the study period. There were 109 cases of premature rupture of fetal membranes, out of which 60 (0.9%) were cases of preterm PROM, whereas 49 (0.7%) were cases of term PROM. Hence, the prevalence of PROM over the study period was 1.6%. The duration of membrane rupture has shown a statistically significant association with neonatal outcome with patients presenting within 24 h of membrane rupture having better outcomes.Conclusion:The prevalence of preterm and term PROM in this study was low and majority of the patients had active management with good neonatal outcome. The duration of membrane rupture affects neonatal outcome.